Evaluating the Effectiveness and Efficiency of a Training Program for Tunnel Construction Workers - Zongyong Guo; Huadi Tao; Yanqun Yang; Wei Lin (Buildings)
With the benefits of reduced travel time and alleviated traffic congestion, tunnel construction significantly enhances urban mobility. Meanwhile, tunnel construction accidents result in many casualties and property losses. To minimize accidents associated with tunnel construction while keeping its benefits, it is important to enhance the effectiveness and efficiency of training programs for construction workers. However, there is a lack of training evaluation systems specifically designed for tunnel construction workers, along with limited research on the effectiveness and efficiency of training programs for this group. This paper targets personnel from the China Railway 14th Bureau Group Company, aiming to evaluate a training program designed for tunnel construction workers. Three popular training approaches are proposed to evaluate the effectiveness and efficiency of training outcomes, including WeChat push safety construction knowledge (WP), the emergency drill (ED), and the unitive lecture (UL). Additionally, a concept of study is conducted to examine the performance of the proposed approaches in eighteen schemes that vary at different levels of training intensity by using VR (virtual reality), an electroencephalogram (EEG) system, and data enveloping analysis (DEA). The results show that the ED is the most effective training method, enabling industry professionals to respond effectively to unsafe situations by equipping them with critical skills through comprehensive training. Additionally, the ED has great potential for training tunnel construction workers via the provision of simulated experiences to enhance their safety preparedness.